Mister X - Lutz, John, 1939- (Pinnacle Books, 2010)
He mutilates his victims. Slices their throats. And carves an X into their flesh. Five years ago, he claimed the lives of six women. Then the killings abruptly stopped, no one knows why. Ex-homicide detective Frank Quinn remembers. Which is why he's shocked to see one of the dead women in his office. Actually, she's the identical twin of the last victim, and she wants Quinn to find her sister's murderer. But when the cold case heats up, it attracts the media spotlight and suddenly the killings start again.